A Study of the Adaptive Reuse Concept in Colonial Buildings in the Jalan Kawi Area, Malang City - Aldika Prananda Vebrino siregar; Gatot Adi Susilo (Program Studi Arsitektur, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2026)
The Kawi Street area in Malang City contains a number of colonial buildings that have the potential to be preserved through the concept of adaptive reuse, which allows changes in the function of old buildings without eliminating their historical and architectural values. This study aims to explore the potential application of adaptive reuse to colonial buildings along Kawi Street by analyzing the opportunities, challenges, and impacts of this strategy on area sustainability and urban revitalization. Using a descriptive qualitative approach involving field observations, interviews with stakeholders, and a review of relevant literature, the study finds that although many colonial buildings in this area remain suitable for revitalization, there are constraints related to preservation regulations and public awareness of architectural heritage values. On the other hand, adaptive reuse can provide economic and social benefits, such as increased tourism attractiveness and the creation of sustainable public spaces. Therefore, synergy between the government, the community, and relevant stakeholders is required to implement this strategy effectively.